PROBLEM LEARNING IN PRIMARY SCHOOL AS MEANS OF FORMATION ACTIVE, CREATIVE, CONSCIOUS PERSONALITIES (Pedagogy of Higher and Secondary Education, 2002)
The arficle deals with the principal ways of creating situations containing some problems at the lessons of the native language on the primary school level. The system o f particular learning problems offered in the article greatly contributes in the form ation of active, creative and conscious personality.